1996
DOI: 10.1002/(sici)1099-1581(199604)7:4<234::aid-pat528>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating Polymer Networks Based on Polyurethane and Poly(butyl methacrylate): Interrelation Between Reaction Kinetics and Microphase Structure

Abstract: The effect of the reaction kinetics on the formation of semi‐IPNs based on crosslinked polyurethane and linear poly(butyl methacrylate) of various compositions has been studied. New data are presented concerning the interconnection between the reaction kinetics, gelation and rheokinetics of IPN formation, between kinetics and crosslinking density, microphase structure and degree of microphase separation. It was shown that kinetic factors determine the conditions of microphase separation and formation of microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The following investigations on IPNs have fully confirmed the concept5–8, 11 that the simultaneous chemical reactions are accompanied by phase separation. In Reference 7 for the first time, it was shown that phase separation in IPNs proceeds according to spinodal mechanism.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The following investigations on IPNs have fully confirmed the concept5–8, 11 that the simultaneous chemical reactions are accompanied by phase separation. In Reference 7 for the first time, it was shown that phase separation in IPNs proceeds according to spinodal mechanism.…”
Section: Introductionmentioning
confidence: 53%
“…However, analysis of the conditions of phase separation during chemical reaction and their interconnection with the reaction kinetics have not been investigated up to now. Meanwhile, for interpenetrating polymer networks (IPN), there are many papers showing the interdependence between chemical reactions of the formation of two independent networks and phase separation 2–11. Formation of IPNs is based on the simultaneous reactions of the synthesis of two cross‐linked polymers under conditions where each polymer is formed according its own reaction mechanism (for example, radical polymerization and polycondensation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of IPN formation proceeds at conditions accompanied by the transition from the one-phase to two-phase state in the course of reaction at a de nite conversion degree. As a result, a two-phase system is formed with phases differing in their composition, the latter being dependent on the kinetic conditions of reaction [11]. IPN may be considered as 'chemical' alloys and have all the features typical of alloys of linear polymers.…”
Section: Thermodynamic Approachmentioning
confidence: 97%
“…A fundamental phenomenon associated with nearly all IPNs is phase separation. Although a huge effort has been made,3–8 the effect of morphology on the mechanical damping of IPNs has not yet been clearly understood. Until recently,9, 10 IPN interphase content could not be analyzed quantitatively.…”
Section: Introductionmentioning
confidence: 99%